2010
DOI: 10.1016/s1413-8670(10)70118-5
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity rates for toxoplasmosis, rubella, syphilis, cytomegalovirus, hepatitis and HIV among pregnant women receiving care at a Public Health Service, São Paulo State, Brazil

Abstract: Infectious and parasitic diseases affecting women during their reproductive age may result in vertical transmission. The aim of this study was to determine the seroprevalence for TORSCH among pregnant women receiving care at a university hospital. Records of 574 pregnant women who received medical attention from January 2006 to December 2007 were assessed. The mean age was 27.2 ± 6.5 years ranging from 13 to 44. The results of the immunodiagnostic tests were: 62.0% (345/556) for IgG and 3.4% (19/556) for IgM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 23 publications
4
16
0
7
Order By: Relevance
“…Our results showed that 64.4% of the women with high-risk pregnancies had toxoplasmosis. These data suggest that the rate of positive findings of T. gondii infection was high in this group and thus corroborate other studies from the same region of the state of São Paulo 20,23 and from other Brazilian states. [15][16][17][24][25][26][27][28] The similarities between this and other studies carried out in some Brazilian states [15][16][17]28 may reflect homogeneity regarding the laboratory diagnostic strategies used.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that 64.4% of the women with high-risk pregnancies had toxoplasmosis. These data suggest that the rate of positive findings of T. gondii infection was high in this group and thus corroborate other studies from the same region of the state of São Paulo 20,23 and from other Brazilian states. [15][16][17][24][25][26][27][28] The similarities between this and other studies carried out in some Brazilian states [15][16][17]28 may reflect homogeneity regarding the laboratory diagnostic strategies used.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the data collected before 2003 among women of childbearing age showed 66.5%–85.5% seropositivity for anti‐rubella virus IgG. Rubella seroprevalence reported in previous international studies ranged between 85.5% and 93% [1,3]. Comparison of seroprevalence levels between studies is difficult owing to the different designs, sampling, timing of studies in relation to previous outbreaks, variability of laboratory procedures, and titer cut‐off points used to define positivity of anti‐rubella IgG.…”
Section: Descriptive and Analytical Data For Rubella Immunity In The mentioning
confidence: 91%
“…Clinical diagnosis of cerebral toxoplasmosis in HIV-infected patients was based on: 1) progressive neurological deficits; 2) contrast-enhancing mass lesion(s) on computed tomography and/or magnetic resonance imaging; and 3) successful clinical and radiological response to antiparasitic treatment within 10-14 days [13,14]. Pregnant women with suspicion of acute toxoplasmosis infection were admitted and treated at the High-Risk Antenatal Care and Fetal Medicine Service (Hospital de Base, Sao José do Rio Preto, Brazil) After enrolling in a high-risk pregnancy clinic, pregnant women were routinely screened for TORSCH (Toxoplasmosis, Rubella, Syphilis, Cytomegalovirus, Hepatitis and HIV) [37,38] Those clinically, epidemiologically suspected of toxoplasmosis and having positive IgM or low IgG avidity for anti-T. gondii antibodies were underwent to amniocentesis and peripheral blood for PCR. Before collection pregnant women were informed of the procedure and signing informed-consent forms.…”
Section: Clinical Samplesmentioning
confidence: 99%